Ultra-thin Fe–Si alloy sheet with excellent high frequency magnetic properties fabricated by partial decarburization combined with multi-stage cold rolling. (February 2023) - Na, Jungkyun; Ko, Hyun-seok; Koo, Yangmo; Park, Semin
Abstract: Transformers with high operating frequencies are highly advantageous owing to their compact sizes. To improve their performance, we successfully fabricated ultra-thin Fe–Si alloy sheets using a novel partial decarburization and multistage cold rolling method. The sheets comprised a high volume fraction of uniform grains under 50 μm with 〈001〉 // rolling direction (RD) texture (78%) and displayed excellent magnetic properties at 20 kHz. Importantly, it was verified that core loss could be controlled by the growth of 〈001〉 // RD grains, and grain size was affected by the sheet thickness and annealing time. The 〈001〉 // RD grains were well developed for sheet thicknesses of 0.05mm–0.07 mm; however, under 0.05 mm, Goss grain growth was hindered by the thickness of the thin sheet. Our specimen achieved a core loss (P0.5/20, 000 ) improvement of about 20% (4.54 W/kg) and one of the highest magnetic flux densities (1.80T) compared with commercial Fe-Si alloy sheets. Graphical abstract: Image, graphical abstract